Identification and functionality prediction of pathogenesis-related protein 1 from legume family - Tellis, Meenakshi; Mathur, Monika; Gurjar, Gayatri; Kadoo, Narendra; Gupta, Vidya (Proteins-Structure Function and Bioinformatics, 2017)
The production and accumulation of pathogenesis-related (PR) proteins in plants is one of the important responses to biotic and abiotic stress. Large number of identified PR proteins has been categorized into 17 functional families based on their structure, phylogenetics, and biological activities. However, they are not widely studied in legume crops. Using 29 PR1 proteins from Arabidopsis thaliana, as query, here we have predicted 92 candidate PR1 proteins through the PSI-BLAST and HMMER programs. These candidate proteins were comprehensively analyzed with, multiple sequence alignment, domain architecture studies, signal peptide, and motif extraction followed by phylogenetic analysis. Further, response of two candidate PR1 proteins from chickpea against Fusarium oxysporum f.sp.ciceri attack was validated using qRT-PCR followed by their 3D structure prediction. To decipher mode of action for PR1s, docking of pathogen extracellular matrix components along with fungal elicitors was performed with two chickpea PR1 proteins. Based on these findings, we propose carbohydrate to be the unique pathogen-recognition feature for PR1 proteins and beta-glucanase activity via beta-glucan binding or modification.

Plant-pathogen interactions: microRNA-mediated trans-kingdom gene regulation in fungi and their host plants - Mathur, Monika; Nair, Aswathy; Kadoo, Narendra (Genomics, 2020)
MicroRNAs (miRNAs) have been prevalently studied in plants, animals, and viruses. However, recent studies show evidences of miRNA-like RNAs (milRNAs) in fungi as well. It is known that after successful infection, pathogens hijack the host machinery and use it for their own growth and multiplication. Alternatively, resistant plants can overcome the pathogen attack by a variety of mechanisms. Based on this prior knowledge, we computationally predicted milRNAs from 13 fungi, and identified their targets in transcriptomes of the respective fungi as well as their host plants. The expressions of the milRNAs and targets were confirmed using qRT-PCR. We found that plant miRNAs targeted fungal virulence genes, while fungal milRNAs targeted plant resistance genes; corroborating miRNA-mediated trans-kingdom gene regulation and the roles of miRNAs in plantpathogen interactions. Transgenic plants with miRNAs targeting fungal virulence genes, or anti-sense of fungal milRNAs, would be expected to be highly resistant to the fungal pathogens.
Keywords: Disease resistance; Fungal miRNAs; qRT-PCR; Resistance genes; Target prediction; Virulence genes